A solid-state electrolyte prepared based on 3D printing and a preparation method and application thereof

CN122992153APending Publication Date: 2026-10-27LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611290572.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]有鉴于此,本发明的目的在于提供一种基于3D打印制备得到的固态电解质及其制备方法和应用,以解决现有技术中固态电解质薄膜制备精度低、致密度不足、边缘覆盖不完整以及多层异质电解质层间界面阻抗高的技术问题

Benefits of technology

本发明将传统湿法涂布的“机械涂布-溶剂挥发”流程转变为3D打印的“光控原位固化-热处理致密化”,重构了薄膜制备流程,最终获得的电解质膜具有精度高、致密度高、缺陷少的特点,此外可以突破传统热力学限制,原位生成具有低层间界面阻抗特性的多层异质复合固态电解质薄膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a solid-state electrolyte prepared based on 3D printing and a preparation method and application thereof, and belongs to the technical field of batteries. The preparation method comprises the following steps: mixing solid-state electrolyte powder, a binder containing an unsaturated double bond and a solvent to prepare a slurry; making a substrate fully contact with the slurry, so that the slurry coats the surface of the substrate; irradiating the substrate coated with the slurry with ultraviolet light, so that the binder is crosslinked and solidified in situ to form a composite thin film blank containing the solid-state electrolyte; and performing heat treatment on the composite thin film blank to densify. The solid-state electrolyte is at least one of a sulfide, a halide or an oxide solid-state electrolyte. The application can also prepare a multilayer heterogeneous solid-state electrolyte composite thin film containing at least two layers of different electrolyte materials by repeating the steps of immersion and ultraviolet light solidification and performing integrated heat treatment at the end.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, specifically relating to a solid electrolyte prepared by 3D printing, its preparation method, and its application. Background Technology

[0002] Solid-state batteries are considered a crucial development direction for next-generation electrochemical energy storage devices due to their advantages such as high energy density, high safety, and wide operating temperature range. Solid-state electrolytes, as the core component of solid-state batteries, directly determine the overall performance of the battery. Currently, solid-state electrolytes are mainly classified into three categories: polymer solid-state electrolytes, oxide solid-state electrolytes, and sulfide / halide solid-state electrolytes. Polymer solid-state electrolytes (such as PEO-based and PVDF-HFP-based electrolytes) have advantages such as good flexibility, good processability, and good interfacial contact, but their room-temperature ionic conductivity is relatively low (typically 10). -5 ~10 -4 Solid-state electrolytes (S / cm) have a narrow electrochemical window, making them unsuitable for high-power applications. Oxide solid-state electrolytes (such as LLZO and LAGP) have wide electrochemical windows and are stable to lithium, but they are rigid, have poor solid-solid interface contact, and traditional molding methods require high-temperature sintering (often exceeding 1000℃), making direct film formation on current collectors impossible. Sulfide / halide solid-state electrolytes (such as Li6PS5Cl and Li3InCl6) have the highest room-temperature ionic conductivity (up to 10). -3 ~10 -2 With a sulfur / halide ratio of 0.5 g / cm and a soft texture that can be cold-pressed, it is considered the most promising solid electrolyte system for industrialization. However, sulfur / halide electrolytes are chemically reactive and extremely sensitive to moisture, oxygen, and polar solvents, which imposes stringent requirements on the preparation process.

[0003] Studies have shown that the fabrication process of solid electrolyte films directly affects their final performance. In particular, the fabrication precision and density of solid electrolyte films directly determine the interfacial impedance and cycle life of all-solid-state batteries. Currently, the widely used industrial wet coating process mixes solid electrolyte powder with binders and solvents to form a slurry, which is then coated onto substrates such as metal foils and dried to form a film. However, the wet coating process has the following inherent defects in the fabrication of solid electrolyte films: First, the coating thickness accuracy is poor, typically with an error on the order of ±10 μm, making it difficult to meet the precision requirements of ultrathin films; second, the density is low, relying on solvent evaporation to form the film, which inevitably generates a large number of pores during the drying process, leading to poor solid-solid interface contact; third, incomplete edge coverage occurs, with the slurry shrinking at the edge of the current collector due to surface tension, resulting in exposed foil after drying and creating a short-circuit hazard; fourth, heterogeneous composites are difficult, as multilayer electrolytes can only be fabricated separately and then mechanically bonded, leaving micron-level gaps between layers and drastically increasing the interfacial impedance. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide a solid electrolyte prepared by 3D printing, its preparation method and application, so as to solve the technical problems of low precision, insufficient density, incomplete edge coverage and high interfacial impedance between multilayer heteroelectrolytes in the prior art.

[0005] The purpose of this invention is to provide a method for preparing solid electrolytes based on 3D printing. This method is compatible with three types of solid electrolyte materials: sulfides, halides, and oxides. It achieves high-precision control of film thickness and surface morphology, and can prepare multilayer heterogeneous composite films composed of different types of solid electrolytes through layer-by-layer printing and integrated heat treatment. In the obtained composite film, a seamless interlocking interface transition region is formed between adjacent electrolyte layers, with extremely small interlayer gaps. This fundamentally eliminates mechanical bonding interfaces, significantly reduces the interfacial impedance between heterogeneous layers, and simultaneously achieves high density, high ionic conductivity, and zero leakage current collector defects.

[0006] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a solid electrolyte, comprising the following steps: S1: Prepare a slurry containing solid electrolyte powder, a binder with unsaturated double bonds, and a solvent; S2: Ensure that the substrate and the slurry are in full contact, and that the slurry coats the surface of the substrate; S3: The substrate coated with the slurry is irradiated with ultraviolet light to cause the binder to crosslink and cure in situ, forming a blank containing the solid electrolyte; S4: The blank is heat-treated to densify it, thereby obtaining a solid electrolyte.

[0007] Preferably, the solid electrolyte is selected from at least one of sulfide solid electrolytes, halide solid electrolytes, or oxide solid electrolytes.

[0008] Preferably, the sulfide solid electrolyte includes at least one of Argyrodite-type sulfide solid electrolyte, thio-LISICON-type sulfide solid electrolyte, or LGPS-type sulfide solid electrolyte; the chemical formula of the Argyrodite-type sulfide solid electrolyte is Li. 6-a PS 5-a X 1+a Where 0≤a≤1, X includes at least one of Cl, Br or I; the sulfide solid electrolyte is synthesized using a micro-sulfur excess process, with the excess sulfur molar percentage being 0.5%~5.0%.

[0009] Preferably, the oxide solid electrolyte includes at least one of garnet-type oxide solid electrolyte, perovskite-type oxide solid electrolyte, LISICON-type oxide solid electrolyte, NASICON-type oxide solid electrolyte, anti-perovskite-type oxide solid electrolyte, or LiPON-type oxide solid electrolyte.

[0010] Preferably, the general formula of the halide solid electrolyte is A a -M m -X b Wherein, A is selected from Li or Na, M is selected from one or more of Sc, Y, La-Lu, Zr, Hf, Nb, Ta, Al, Ga, In, Mg, Mn, Fe, Co, Zn or Cd, and X is selected from at least one of F, Cl, Br or I.

[0011] Preferably, when the solid electrolyte is selected from a sulfide solid electrolyte, the solvent is selected from at least one of toluene, xylene, cyclohexane, n-heptane, butyl acetate, ethyl propionate, isobutyl isobutyrate, butyl hexanoate, dibutyl ether, anisole, or 3-heptanone, and the slurry does not contain a photoinitiator. The mass ratio of the sulfide solid electrolyte, binder, and solvent is (10~70):(0.5~20):(30~90).

[0012] Preferably, when the solid electrolyte is selected from a halide solid electrolyte, the solvent is selected from at least one of toluene, xylene, cyclohexane, n-heptane, butyl acetate, ethyl propionate, isobutyl isobutyrate, butyl hexanoate, dibutyl ether, anisole, or 3-heptanone, and the slurry further includes a first photoinitiator; the first photoinitiator is selected from at least one of benzoin dimethyl ether, 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, benzophenone, or isopropylthioxanthraphenone; wherein, the mass ratio of the halide solid electrolyte, binder, first photoinitiator, and solvent is (30~60):(0.5~10):(0.01~2):(30~70).

[0013] Preferably, when the solid electrolyte is selected from oxide solid electrolytes, the solvent is selected from at least one of toluene, xylene, cyclohexane, n-heptane, butyl acetate, ethyl propionate, isobutyl isobutyrate, butyl hexanoate, dibutyl ether, anisole, or 3-heptanone, and the slurry further includes a second photoinitiator; the second photoinitiator is selected from at least one of α-hydroxy ketone photoinitiators, benzoyl ketal photoinitiators, acylphosphine oxide photoinitiators, benzophenone photoinitiators, or thioxanthone photoinitiators; wherein, the mass ratio of the oxide solid electrolyte, binder, second photoinitiator, and solvent is (30~60):(0.5~10):(0.01~2):(30~70).

[0014] Preferably, the binder containing unsaturated double bonds is selected from at least one of the following: modified polyisobutylene, modified hydrogenated nitrile butadiene rubber, modified nitrile butadiene rubber, modified polyacrylic acid, modified polymethyl methacrylate, modified styrene-ethylene-butene-styrene block copolymer, modified styrene-butadiene rubber, modified hydrogenated styrene-butadiene rubber, modified styrene-ethylene-ethylene-propylene-styrene block copolymer, modified polyimide, modified polyvinylidene fluoride, modified butyl rubber, modified polytetrafluoroethylene, modified polypropylene, modified polyethylene, modified cis-butadiene rubber, modified vinyl polybutadiene rubber, modified isoprene rubber, modified ethylene propylene diene monomer (EPDM) rubber, or modified ethylene propylene diene monomer (EPDM) rubber.

[0015] Preferably, the molecular weight of the binder containing unsaturated double bonds is 1 × 10⁻⁶. 4 ~1×10 8 .

[0016] In the binder containing unsaturated double bonds, the content of unsaturated double bonds is 0.1% to 15% by mass, such as 0.1%, 0.5%, 0.8%, 1%, 3%, 5%, 8%, 10%, 12%, or 15%. The content of unsaturated double bonds can be determined by the iodine value method.

[0017] In this invention, the "modified adhesive" or "adhesive containing unsaturated double bonds" mentioned above refers to the corresponding polymers whose molecular chains contain unsaturated double bonds. Such adhesives are commercially available. The molecular weight and double bond content of commercially available products should be within the range defined in this invention. Those skilled in the art can also prepare modified polymers containing unsaturated double bonds using existing known grafting methods; however, this invention preferably uses commercially available adhesives containing unsaturated double bonds directly to simplify the process.

[0018] Preferably, the substrate includes at least one of copper foil, aluminum foil, stainless steel foil, carbon-coated aluminum foil, PET, PI, PP or PE.

[0019] Preferably, the thickness of the substrate is 5~30 μm.

[0020] Preferably, the substrate is in full contact with the slurry by immersing the substrate in the slurry.

[0021] Preferably, the wavelength of the ultraviolet light irradiation is 200~400 nm; the duration of the ultraviolet light irradiation is 0.1 s~600 s, more preferably 1 s~120 s, and even more preferably 5 s~60 s.

[0022] Preferably, the heat treatment is carried out under an argon or nitrogen protective atmosphere, the heat treatment temperature is 50℃~300℃, and the heat treatment time is 0.1~24 h.

[0023] Preferably, the steps of preparing the slurry, ensuring full contact between the substrate and the slurry, and irradiating with ultraviolet light are carried out in a dry environment with a dew point below -40°C.

[0024] Preferably, step S4 of the preparation method is: After step S3 is completed and a blank containing the solid electrolyte is obtained, the blank is immersed again in a slurry containing a different type of solid electrolyte powder than that in step S1, so that the slurry is in full contact with the surface of the blank, and ultraviolet light is applied to allow the latter layer of slurry to penetrate into the micropores of the former layer of blank and solidify, forming a multilayer composite blank; then the multilayer composite blank is heat-treated to form an interface transition zone between adjacent electrolyte layers, resulting in a multilayer heterogeneous solid electrolyte containing at least two layers of different solid electrolytes.

[0025] Secondly, the present invention provides a solid electrolyte, which is prepared according to the preparation method described above. The solid electrolyte comprises solid electrolyte particles and a crosslinking binder network, wherein the crosslinking binder network is formed by crosslinking and curing of a polymer containing unsaturated double bonds under ultraviolet light and by heat treatment.

[0026] Preferably, the solid electrolyte comprises a multilayer heterostructure of at least two layers of different solid electrolyte materials, with an interface transition region between adjacent electrolyte layers.

[0027] Thirdly, the present invention provides a solid-state battery, which includes a positive electrode, a negative electrode, and a solid electrolyte disposed between the positive electrode and the negative electrode, wherein the solid electrolyte is the solid electrolyte involved in the above-mentioned technical solution.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention transforms the traditional wet coating process of "mechanical coating-solvent evaporation" into the 3D printing process of "photo-controlled in-situ curing-thermal densification", reconstructing the thin film preparation process. The resulting electrolyte film has the characteristics of high precision, high density and few defects. In addition, it can break through the traditional thermodynamic limitations and generate multilayer heterogeneous composite solid electrolyte films with low interlayer interface impedance in situ.

[0029] Specifically, the thickness of traditional wet coating depends on the doctor blade gap and slurry rheology, while solvent evaporation during drying leads to significant volume shrinkage, resulting in low precision and uncontrollability. This invention precisely controls the curing depth by selecting the ultraviolet light wavelength: different wavelengths have different absorption coefficients of photoactive materials. According to the Beer-Lambert law, light intensity decays exponentially within the slurry, and curing only occurs in shallow regions where the light intensity is above the polymerization threshold. Strong absorption wavelengths allow for extremely shallow light penetration, yielding submicron-sized films; weak absorption wavelengths allow for deeper penetration, yielding films tens of micrometers in diameter. The thickness is thus transformed into an optical parameter determined by the wavelength, eliminating mechanical fluctuations and solvent shrinkage, achieving precise control at the ±1 μm level. Simultaneously, ultraviolet light-induced cross-linking polymerization instantly locks electrolyte particles into a three-dimensional network within milliseconds to seconds. In the subsequent integrated heat treatment, the binder further solidifies, resulting in dense particle fusion. Due to the uniformity of the initial preform, the density after heat treatment and compaction can reach over 95%, providing a continuous channel for ion conduction and significantly improving ionic conductivity. Full edge coverage and customizable surface morphology are also extensions of optical control precision: the substrate is immersed in the slurry, and the curing speed is faster than the edge retraction caused by surface tension, thereby accurately replicating the exposure area, achieving 100% coverage, and eliminating the risk of short circuit due to exposed foil; combined with patterned exposure, micropillars or pit arrays can be constructed on the film surface to increase the effective contact area and anchor the interface, further reducing the interface impedance.

[0030] For multilayer heterogeneous composites, a single heat treatment following layer-by-layer printing replaces separate coating, drying, and mechanical bonding. Mechanical bonding only forms point contacts at the micron-level rough peaks, leaving nanometer-sized air gaps between layers, requiring ions to overcome high energy barriers to cross the membrane. In this invention, the subsequent slurry penetrates the micropores of the preceding preform film, forming a network interlocking during curing, achieving gapless contact at the microscopic level. During subsequent co-heat treatment, atoms on both sides of the interface interdiffusion under the concentration gradient, generating a gradually changing interfacial transition zone, replacing the original sharp heterogeneous interface with a chemically bonded continuous conductive layer. This seamless interlocking structure significantly reduces the ion migration barrier, and the interfacial impedance can be reduced by an order of magnitude compared to mechanically bonded components. The ability of the aforementioned layer-by-layer composite to accommodate sulfides, halides, and oxides is attributed to the initiation design tailored to their respective chemical properties: the trace amounts of elemental sulfur precipitated in situ on the surface of the sulfide solid electrolyte are themselves photoactive components, directly initiating binder polymerization upon absorption of ultraviolet light, without the need for any potentially destructive initiators; the halide electrolyte, being a Lewis acid, utilizes a non-Lewis base photoinitiator without basic groups, avoiding slurry failure due to acid-base coordination and ensuring chemical stability and effective curing. These designs enable various electrolytes to construct dense and highly conductive films through a unified photocuring-thermal treatment process, achieving perfect fusion in integrated heat treatment, ultimately resulting in multilayer heterogeneous composite solid electrolyte films with significantly enhanced performance. Attached Figure Description

[0031] Figure 1 This is a SEM image of the cross-section of the 3D-printed high-precision sulfide solid electrolyte film obtained in Example 1; Figure 2 This is a photograph of the 3D-printed high-precision oxide electrolyte film obtained in Example 3. Figure 3 This is a SEM image of the cross-section of the multilayer heterogeneous composite electrolyte film prepared in Example 5; Figure 4 The image shown is an EDS image of the cross-section of the multilayer heterogeneous composite electrolyte film prepared in Example 5. Figure 3 EDS image corresponding to the SEM-captured area. Detailed Implementation

[0032] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0033] This invention provides a method for preparing a solid electrolyte, comprising the following steps: S1: Prepare a slurry containing solid electrolyte powder, a binder with unsaturated double bonds, and a solvent; S2: Ensure that the substrate and the slurry are in full contact, and that the slurry coats the surface of the substrate; S3: The substrate coated with the slurry is irradiated with ultraviolet light to cause the binder to crosslink and cure in situ, forming a blank containing the solid electrolyte; S4: The blank is heat-treated to densify it, thereby obtaining a solid electrolyte.

[0034] According to the present invention, a slurry comprising solid electrolyte powder, a binder containing unsaturated double bonds, and a solvent is first prepared.

[0035] The binder used in this invention is a polymer containing a small number of unsaturated double bonds, whose molecular chains contain unsaturated functional groups (such as carbon-carbon double bonds C=C) capable of undergoing free radical polymerization. Under ultraviolet light irradiation, the photoactive components (photoinitiators or nanoscale elemental sulfur / polysulfides on the surface of sulfide solid electrolytes) absorb light energy to generate free radicals, initiating a cross-linking reaction of the unsaturated double bonds on the binder molecular chains, forming a three-dimensional cross-linked network structure within milliseconds to seconds. This cross-linked network uniformly anchors the solid electrolyte particles in three-dimensional space, avoiding the pores caused by particle rearrangement during traditional solvent evaporation film formation. The cross-linking and curing speed is faster than the edge retraction caused by surface tension, thus achieving complete coverage of the substrate edges.

[0036] The cross-linked network formed by the binder exists only as a mechanical support framework; ion conduction mainly occurs through grain boundaries and the lattice between solid electrolyte particles. The selectable molecular weight of the binder is relatively wide (1×10⁻⁶). 4 ~1×10 8 Preferably 1×10 5 ~1×10 7 Within this range, films that balance flexibility and mechanical strength can be obtained.

[0037] In some embodiments of the present invention, the adhesive includes modified polyisobutylene (hereinafter referred to as modified PIB), hydrogenated nitrile butadiene rubber (hereinafter referred to as modified HNBR), modified nitrile butadiene rubber (hereinafter referred to as modified NBR), modified polyacrylic acid (hereinafter referred to as modified PAA), modified polymethyl methacrylate (hereinafter referred to as modified PMMA), modified styrene-ethylene-butene-styrene block copolymer (hereinafter referred to as modified SEBS), modified styrene-butadiene rubber (hereinafter referred to as modified SBR), hydrogenated styrene-butadiene rubber (hereinafter referred to as modified HSBR), modified styrene-ethylene-ethylene-propylene-styrene block copolymer (hereinafter referred to as modified SEEPS), modified polyimide (hereinafter referred to as modified PI), modified polyvinylidene fluoride (hereinafter referred to as modified PVDF), and modified butyl rubber (hereinafter referred to as modified II). Modified polytetrafluoroethylene (PTFE), modified polypropylene (PP), modified polyethylene (PE), modified butadiene rubber (BR), modified vinyl polybutadiene rubber (HVBR / HMBR), modified isoprene rubber (IR), modified ethylene propylene diene monomer (EPM), modified ethylene propylene diene monomer (EPDM), and one or more of the above-mentioned polymer modification varieties, with a small amount of unsaturated functional groups added to the original molecular chain structure; preferably modified PIB, modified HNBR, modified NBR, modified SEBS, modified SBR, modified HSBR, modified SEEPS, modified PMMA, or modified IIR.

[0038] It should be specifically noted that, in this invention, the solid electrolyte includes at least one of sulfide solid electrolytes, halide solid electrolytes, and oxide solid electrolytes. Based on the different chemical properties of various types of solid electrolytes, this invention employs differentiated photoinitiation strategies: (1) When the solid electrolyte is a sulfide solid electrolyte, the sulfide solid electrolyte is prepared using a micro-sulfur excess process, with a sulfur excess molar percentage of 0.5% to 5.0%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%, etc. Nanoscale elemental sulfur or polysulfides are precipitated on the surface of the sulfide solid electrolyte particles as photoinitiating components. The meaning of the sulfur excess molar percentage is the percentage of additional sulfur element introduced during the preparation of the sulfide solid electrolyte, according to the target sulfide electrolyte chemical formula (e.g., Li). 5.5 PS 4.5 Cl 1.0 Br 0.5 Calculate the percentage of the total stoichiometric moles of sulfur required.

[0039] In this invention, the sulfide solid electrolyte includes at least one of Argyrodite-type sulfide solid electrolyte, thio-LISICON-type sulfide solid electrolyte, or LGPS-type sulfide solid electrolyte; the chemical formula of the Argyrodite-type sulfide solid electrolyte is Li. 6-a PS 5-a X 1+a , where 0≤a≤1, such as 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, and X includes at least one of Cl, Br or I.

[0040] This invention employs a process of using a trace amount of excess sulfur (preferably 0.5% to 5.0% molar excess) during the synthesis of sulfide solid electrolytes, causing the excess sulfur to precipitate on the surface of electrolyte particles, forming nanoscale elemental sulfur or polysulfides. These elemental sulfur / polysulfides absorb light energy under ultraviolet light irradiation, generating free radicals or photogenerated electrons through photoexcitation, thereby initiating a free radical polymerization reaction of the unsaturated double bonds on the binder molecular chain.

[0041] It should be noted that when the excess sulfur molar percentage is less than 0.5%, the excess sulfur element forming elemental sulfur / polysulfides is insufficient to initiate binder polymerization; when the excess sulfur molar percentage exceeds 5.0%, elemental sulfur / polysulfides act as Li + Poor conductors can coat the surface of sulfide electrolytes, severely hindering Li + The preferred transmission range is 0.5% to 5%, within which sufficient photoinitiation efficiency can be guaranteed without significantly negatively impacting ionic conductivity.

[0042] Furthermore, since the elemental sulfur / polysulfides on the surface of the sulfide solid electrolyte itself act as photoinitiators, no external photoinitiators are required, thus avoiding the risk of chemical reactions between the external photoinitiators and the sulfide solid electrolyte and maintaining the integrity of the ion conduction channels of the sulfide solid electrolyte.

[0043] (2) When the solid electrolyte is a halide solid electrolyte, the slurry also contains a first photoinitiator, and the first photoinitiator is a non-Lewis base photoinitiator.

[0044] Halogenated solid electrolytes (such as Li3InCl6, Li3YCl6, etc., with the general formula A) a -M m -X b The halides, wherein A is Li or Na, M is one or more of Sc, Y, La-Lu, Zr, Hf, Nb, Ta, Al, Ga, In, Mg, Mn, Fe, Co, Zn, and Cd, and X is one or more of F, Cl, Br, and I; a, m, and b are positive numbers and satisfy the electroneutrality condition: a + Σ(n i ×m i )=b, where n i Let n be the oxidation number of the i-th element in M. i The photoinitiator is selected from one or more of +2, +3, +4, and +5. The halide solid electrolyte exhibits Lewis acidity, meaning its metal cations can undergo coordination reactions with compounds containing basic groups (such as amino, hydroxyl, and carboxyl groups), disrupting the electrolyte's crystal structure or surface chemical environment and leading to a significant deterioration in ionic conductivity. Therefore, this invention selects non-Lewis base photoinitiators without basic groups in the halide electrolyte system, including at least one of benzoin dimethyl ether, 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO), benzophenone, and isopropylthioxanthone (ITX). These photoinitiators do not contain basic groups capable of coordinating with the halide electrolyte, effectively initiating crosslinking and curing of the binder under ultraviolet light irradiation while maintaining the chemical stability of the halide electrolyte.

[0045] (3) When the solid electrolyte is an oxide solid electrolyte, the slurry further contains a second photoinitiator, which is selected from at least one of α-hydroxy ketones, benzoyl ketals, acylphosphine oxides, benzophenones and thioxanthones.

[0046] Oxide solid electrolytes (such as LLZO, LAGP, LATP, etc.) have relatively stable chemical properties. The oxide electrolytes include at least one of garnet-type oxide electrolytes, perovskite-type oxide electrolytes, LISICON-type oxide electrolytes, NASICON-type oxide electrolytes, anti-perovskite-type oxide electrolytes, or LiPON-type oxide electrolytes. Preferably, the oxide electrolytes include at least one of LLZO (lithium lanthanum zirconium oxide), LAGP (lithium aluminum germanium phosphate), or LATP (lithium aluminum titanium phosphate).

[0047] In this invention, the solvent is an inert anhydrous solvent. For sulfide solid electrolytes and halide solid electrolytes, nonpolar or weakly polar solvents are preferred, such as at least one of toluene, xylene, cyclohexane, n-heptane, butyl acetate, ethyl propionate, isobutyl isobutyrate, butyl hexanoate, dibutyl ether, anisole, and 3-heptanone. For oxide solid electrolytes, at least one of acetonitrile, anisole, chloroform, dichloroethane, N,N-dimethylformamide, toluene, xylene, cyclohexane, n-heptane, butyl acetate, ethyl propionate, isobutyl isobutyrate, butyl hexanoate, dibutyl ether, anisole, and 3-heptanone is preferred.

[0048] In some embodiments of the present invention, the mass ratio of the sulfide solid electrolyte, binder, and solvent is (10~70):(0.5~20):(30~90), preferably (30~60):(0.5~10):(40~70), and more preferably (40~55):(1~5):(45~60); the mass ratio of the halide solid electrolyte, binder, first photoinitiator, and solvent is (30~60):(0.5~10):(0.01~2):(30~70), preferably (30~60):(0.5~10). The mass ratio of the oxide solid electrolyte, binder, second photoinitiator, and solvent is (30~60):(0.5~10):(0.01~2):(30~70), preferably (30~60):(0.5~10):(0.05~1.8):(40~70), and more preferably (40~55):(1~5):(0.05~1.5):(45~60).

[0049] In summary, in some embodiments of the present invention, it is preferable to mix solid electrolyte powder, a binder containing unsaturated double bonds, a solvent, and optionally a photoinitiator to prepare a slurry.

[0050] Then, according to the present invention, the substrate is brought into full contact with the slurry, so that the slurry covers the surface of the substrate.

[0051] In some embodiments of the present invention, the substrate being in full contact with the slurry means that the substrate is immersed in the slurry.

[0052] The substrate includes at least one of copper foil, aluminum foil, stainless steel foil, carbon-coated aluminum foil, PET, PI, PP or PE; the thickness of the substrate is 5~30 μm, such as 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc.

[0053] Then, according to the present invention, the substrate coated with the slurry is subjected to ultraviolet light irradiation to cause the binder to crosslink and solidify in situ, forming a blank containing the solid electrolyte.

[0054] Traditional wet coating thickness depends on the doctor blade gap and the rheological properties of the slurry, while solvent evaporation during the drying process leads to uncontrollable volume shrinkage. This invention controls the curing depth through selective ultraviolet light irradiation, based on the Beer-Lambert Law.

[0055] In this invention, the wavelength of the ultraviolet light irradiation is 200~400 nm; the duration of the ultraviolet light irradiation is 0.1 s~600 s, preferably 1s~120s, and more preferably 5s~60s.

[0056] The absorption coefficients of photoactive materials (elemental sulfur / polysulfides or added photoinitiators) vary at different wavelengths. For a specific photoactive material, light penetration is extremely shallow in the wavelength region with a high absorption coefficient, allowing for films ranging from submicron to several micrometers thick. Conversely, light penetration is deeper in the wavelength region with a low absorption coefficient, resulting in films tens of micrometers thick. For added photoinitiator systems, the appropriate strong / weak absorption wavelengths are selected based on their absorption spectrum. By selecting the wavelength and intensity of ultraviolet light and matching it with the absorption characteristics of the photoactive material, the film thickness can be precisely controlled within ±1 μm, which is difficult to achieve with traditional wet coating methods (precision ±10 μm).

[0057] In this invention, the steps of preparing the slurry, ensuring full contact between the substrate and the slurry, and irradiating with ultraviolet light are carried out in a dry environment with a dew point below -40°C. This is because excessive moisture can lead to the degradation of sulfide and halide solid electrolytes, generating components with low ionic conductivity.

[0058] Then, according to the present invention, the blank is subjected to heat treatment to densify it, thereby obtaining a solid electrolyte. The heat treatment is carried out under an argon or nitrogen protective atmosphere, and the temperature of the heat treatment is 50°C to 300°C, such as 50°C, 70°C, 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 250°C, 280°C, or 300°C; the heat treatment time is 0.1 to 24 hours, preferably 0.5 to 10 hours, and more preferably 0.5 to 5 hours.

[0059] In some preferred embodiments of the present invention, step S4 of the preparation method is as follows: After step S3 is completed and a blank containing the solid electrolyte is obtained, the blank is immersed again in a slurry containing a different type of solid electrolyte powder than that in step S1, so that the slurry is in full contact with the surface of the blank, and ultraviolet light is applied to allow the latter layer of slurry to penetrate into the micropores of the former layer of blank and solidify, forming a multilayer composite blank; then the multilayer composite blank is heat-treated to form an interface transition zone between adjacent electrolyte layers, resulting in a multilayer heterogeneous solid electrolyte containing at least two layers of different solid electrolytes.

[0060] The purpose of this solution is to address the problems of large interlayer nanoscale gaps and interfacial impedance caused by mechanical bonding of traditional multilayer heterogeneous solid electrolyte films after separate film fabrication. By immersing the first layer of the preform film in different types of electrolyte slurries and photocuring it, the subsequent slurry penetrates into the micropores of the first layer to form a network interlocking. Then, through integrated heat treatment, the interfacial elements are interdiffused to form an interface transition zone with gradually changing composition, achieving seamless chemical bonding between heterogeneous layers. This reduces the interfacial impedance and improves the ionic conductivity and cycle stability of the composite film.

[0061] In some other preferred embodiments of the present invention, the ultraviolet irradiation area can be controlled by patterned modeling, and the adhesive in the preset area can be selectively cured, thereby forming a patterned structure (such as a micropillar array or pit array) on the surface of the solid electrolyte film, achieving customizable surface morphology. The patterned structure can increase the electrode / electrolyte interface contact area and provide physical anchoring points, further reducing interfacial impedance.

[0062] The present invention also provides a solid electrolyte, which is prepared by any of the above preparation methods. The solid electrolyte comprises solid electrolyte particles and a crosslinking binder network. The crosslinking binder network is formed by crosslinking and curing of a polymer containing unsaturated double bonds by ultraviolet light irradiation and heat treatment.

[0063] In some preferred embodiments of the present invention, the solid electrolyte comprises a multilayer heterostructure of at least two layers of different solid electrolyte materials, with an interface transition region between adjacent electrolyte layers.

[0064] The present invention also provides an all-solid-state battery, comprising a positive electrode, a negative electrode, and a solid electrolyte disposed between the positive electrode and the negative electrode, wherein the solid electrolyte is any of the solid electrolytes involved in the above technical solutions.

[0065] To better understand the technical solution of this invention, the innovative points of this invention are explained here: (1) The present invention adopts a 3D printing combined with integrated sintering method, and uses the principle of adjusting the light penetration depth by ultraviolet light wavelength to precisely control the curing thickness, to achieve the preparation of solid electrolyte films with thickness accuracy of ±1 μm and density ≥95% (i.e., porosity ≤5%).

[0066] (2) Based on the different characteristics of the three types of electrolytes, namely sulfides, halides and oxides, this invention designs different slurry formulations, such as: designing a self-initiating system of elemental sulfur on the sulfide surface and a non-Lewis base photoinitiator system for halides, so that all three types of electrolytes can be photocured and have universality.

[0067] (3) The present invention adopts substrate immersion exposure and digital optical patterning technology, and utilizes the principle that the polymerization reaction speed is faster than the surface tension of the slurry edge to obtain an electrolyte film with complete edge coverage and customizable surface microstructure, thus eliminating the risk of short circuit due to exposed foil.

[0068] (4) The present invention adopts a layer-by-layer photocuring printing and integrated co-sintering process, and utilizes the principle of interlocking of interlayer polymer networks and interdiffusion of elements to form chemical bonds to obtain a composite electrolyte film with seamless interlocking between heterogeneous layers, and its interface impedance is reduced to 1 / 3 of that of mechanically bonded electrolyte film.

[0069] To further illustrate the present invention, the following embodiments provide a detailed description. Unless otherwise specified, all experimental materials used in the following embodiments of the present invention are commercially available products.

[0070] The performance testing methods involved are as follows: 1. Ionic conductivity test: Random samples were taken from the electrode sheet using a 10 mm aperture cutting machine and placed into a 10 mm diameter test mold. The sample was pressed into a sheet shape under 360 MPa. Stainless steel was used as the blocking electrode. The electrochemical impedance of the electrolyte membrane in the range of 1 MHz-1 Hz at room temperature was measured using an electrochemical workstation. The ionic conductivity of the electrolyte membrane was calculated.

[0071] 2. Thickness test: The thickness of the electrolyte membrane was tested at nine points using a micrometer, and the average value was calculated as the thickness of the electrolyte membrane.

[0072] 3. Density test: Random samples are taken from the electrode sheet using a 10 mm pore size cutting machine, the mass is weighed, the diameter and thickness are tested, the actual density is calculated, and the porosity of the electrolyte film is calculated by substituting the sample true density. The sample density is then calculated according to the formula: density = 1 - porosity.

[0073] Preparation Example 1 - Trace Sulfur Excess Sulfide Solid Electrolyte Li 5.5 PS 4.5 Cl 1.0 Br 0.5 Powder preparation

[0074] In an argon-atmospheric glove box (water content < 0.1 ppm, oxygen content < 0.1 ppm), lithium sulfide (Li₂S, purity ≥ 99.9%), phosphorus pentasulfide (P₂S₅, purity ≥ 99%), lithium chloride (LiCl, purity ≥ 99.9%), and lithium bromide (LiBr, purity ≥ 99.9%) were weighed according to the target stoichiometric ratio. To ensure a trace excess of sulfur, an additional 2 wt% of P₂S₅ was added based on the required mass of P₂S₅ according to the stoichiometric ratio. All raw materials were placed in a mixing device and mixed thoroughly. After mixing, the resulting powder was heated to 500℃ in a sintering furnace at 2℃ / min and held at that temperature for 10 hours, then cooled to room temperature with the furnace. After depolymerization and refinement, Li₂S₅ with trace amounts of elemental sulfur precipitated on its surface was obtained. 5.5 PS 4.5 Cl 1.0 Br 0.5 Powder. XRD analysis confirmed that the main phase is of the Argyrodite type structure, and XPS surface analysis detected the S8 characteristic peak, confirming that elemental sulfur has been precipitated on the surface of the electrolyte particles.

[0075] The sulfide solid electrolyte powders used in the following examples were all synthesized according to the method of this preparation example.

[0076] Example 1: Preparation of high-precision sulfide solid electrolyte thin films

[0077] Under an inert atmosphere, based on the mass ratio of sulfide solid electrolyte: binder: solvent = 45:3:52, the sulfide solid electrolyte Li, with an excess of 0.5% sulfur during synthesis, was synthesized. 5.5 PS 4.5 Cl 1.0 Br 0.5 The powder was dispersed in p-xylene solvent, and a modified SBR binder was added, wherein the modified SBR had an unsaturated bond content of 5% and a molecular weight of 1.9 × 10⁻⁶. 6Mechanical stirring and homogenization yielded a photocurable sulfide slurry. A trace excess of sulfur precipitated on the electrolyte surface. Aluminum foil was immersed in the slurry and exposed to UV LEDs for 30 seconds. Elemental sulfur absorbed light energy, initiating free radical polymerization of the residual unsaturated bonds in the modified SBR, curing in situ on the aluminum foil surface to form a preliminary film. Heat treatment at 90℃ for 0.5 hours under low dew point conditions yielded a dense sulfide solid electrolyte membrane with an average thickness of 45 μm, with thickness deviations within ±1 μm at multiple measurement points. Scanning electron microscopy showed a dense, pore-free membrane surface, completely covering the center and edges without any foil leakage. The ionic conductivity reached 6.8 × 10⁻⁶. -3 S / cm. The initial density was 85%, which increased to 97% after compaction at 500 MPa.

[0078] The SEM image of the cross-section of the sulfide solid electrolyte film obtained in this embodiment is shown below. Figure 1 As shown.

[0079] Example 2: Preparation of high-precision halide electrolyte thin films

[0080] Under an inert atmosphere, Li3InCl6 halide powder was dispersed in p-xylene solvent according to the mass ratio of halide solid electrolyte: binder: first photoinitiator: solvent = 50:2:0.1:47.9, and modified PIB binder was added, wherein the unsaturated bond content of the modified PIB was 2.5% and the molecular weight was 8.7 × 10⁻⁶. 5 In addition, benzoin dimethyl ether photoinitiator was added. The mixture was mechanically stirred and homogenized to obtain a photocurable halide slurry. Exposure was performed using a UV LED for 20 seconds. The benzoin dimethyl ether photoinitiator absorbed light energy, initiating free radical polymerization of the residual unsaturated bonds in modified PIB, curing in situ on the PET surface to form a preliminary film. Under a low dew point environment, heat treatment at 80℃ for 0.5 hours yielded a dense halide electrolyte membrane with an average thickness of 30 μm, with a thickness deviation within ±1 μm measured at multiple points. Scanning electron microscopy showed a dense, pore-free membrane surface, with complete coverage of the center and edges without any leakage. The ionic conductivity reached 9.6 × 10⁻⁶. -4 S / cm. The initial density was 85%, which increased to 97% after compaction at 500 MPa.

[0081] Example 3: Preparation of high-precision oxide electrolyte films

[0082] Under an inert atmosphere, LLZO oxide powder was dispersed in anhydrous N,N-dimethylformamide (DMF) mixed solvent according to the mass ratio of oxide solid electrolyte: second photoinitiator: binder: solvent = 53:1.8:0.2:45. Modified polymethyl methacrylate (PMMA) containing unsaturated double bonds was added, wherein the unsaturated bond content of the modified PMMA was 2.5% and the molecular weight was 5.4 × 10⁻⁶.7 In addition, 1-hydroxycyclohexylphenyl ketone (PHP) was added as a photoinitiator. The mixture was mechanically stirred and homogenized to obtain a photocurable oxide slurry. Exposure was performed using a UV LED for 22 seconds. The PHP absorbed light energy, initiating free radical polymerization of the residual unsaturated bonds in the modified PMMA, which cured in situ on the aluminum foil surface to form a preliminary film. Under a low dew point environment, heat treatment at 200℃ for 0.5 hours yielded a dense oxide electrolyte membrane with an average thickness of 40 μm, with thickness deviation within ±1 μm measured at multiple points. Scanning electron microscopy showed a dense, pore-free membrane surface, with complete foil coverage at the center and edges. The ionic conductivity reached 1.2 × 10⁻⁶. -4 S / cm. Density is 91%.

[0083] A physical image of the oxide electrolyte film obtained in this embodiment is shown below. Figure 2 As shown.

[0084] Example 4: Preparation of surface-patterned oxide electrolyte films

[0085] In an inert atmosphere glove box with a dew point below -40°C, LATP powder, modified hydrogenated nitrile butadiene rubber (modified HNBR) containing unsaturated double bonds, photoinitiator 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO), and anhydrous N,N-dimethylformamide (DMF) were mixed according to the mass ratio of oxide solid electrolyte: binder: second photoinitiator: solvent = 52:1.9:0.1:46. The modified HNBR had an unsaturated bond content of 3.5% and a molecular weight of 3.5 × 10⁻⁶. 5 A uniform, stable, and sediment-free photocurable LATP slurry was obtained through mechanical stirring and homogenization. A 20 μm thick stainless steel foil substrate was completely immersed in the slurry. A DLP UV light was used to project a pre-designed hexagonal micropillar array pattern onto the substrate for 20 seconds. After vacuum drying at room temperature for 2 hours, the LATP particles were densified by heat treatment at 200°C in an argon atmosphere muffle furnace, and finally naturally cooled to room temperature. A 30 μm thick LATP electrolyte film was obtained, with a micropillar protrusion height of approximately 10 μm and a bottom continuous layer thickness of approximately 20 μm. The ionic conductivity reached 1.0 × 10⁻⁶. -4 S / cm. Density is 96%.

[0086] Example 5: Preparation of sulfide / halide bilayer heterogeneous composite electrolyte film

[0087] First layer printing: Following the formulation and process of Example 1, a layer of sulfide Li is first printed and dried on the aluminum foil. 5.5 PS 4.5 Cl 1.0 Br 0.5The initial preform film is not subjected to high-temperature heat treatment. Second layer printing: The substrate with the sulfide preform film is immersed in the halide Li3YCl6 slurry described in Example 2, and irradiated with ultraviolet light for 50 seconds to solidify and form a second halide preform film on the sulfide layer. It is then dried. Integrated heat treatment: The above-mentioned bilayer composite preform film is subjected to integrated heat treatment at 180°C for 2 hours under argon protection. A dense sulfide / halide bilayer composite film is obtained. Cross-sectional SEM shows that the interface between the two layers is blurred, with no nanoscale cracks. Electrochemical impedance spectroscopy shows that the interfacial impedance of this integrally formed composite film is only 1 / 3 of that of a conventional mechanically bonded bilayer film of the same size, and the total ionic conductivity is 1.8 × 10⁻⁶. -3 The density is S / cm, with an initial density of 84%, which increases to 95% after compaction at 500 MPa.

[0088] The SEM image of the cross-section of the multilayer heterogeneous composite electrolyte film prepared in this embodiment is shown below. Figure 3 As shown, the interface between the sulfide electrolyte layer and the halide electrolyte layer is blurred, and no nanoscale cracks are observed. Correspondingly, the EDS image is shown below. Figure 4 As shown, the difference in elemental composition between the two layers can be observed.

[0089] Example 6: Preparation of sulfide / oxide bilayer heterogeneous composite electrolyte film

[0090] First layer printing: Following the formulation and process of Example 1, a layer of sulfide Li is first printed and dried on the aluminum foil. 5.5 PS 4.5 Cl 1.0 Br 0.5 The initial preform film is not subjected to high-temperature heat treatment. Second layer printing: The substrate with the sulfide initial preform film is immersed in the oxide slurry described in Example 3, and irradiated with ultraviolet light to solidify the sulfide layer, forming a second oxide initial preform film, which is then dried. Integrated heat treatment: The above-mentioned bilayer composite preform film is subjected to integrated heat treatment at 180°C for 2 hours under argon protection. A dense bilayer composite film of sulfide / oxide is obtained. Cross-sectional SEM shows that the interface between the two layers is blurred, and there are no nanoscale cracks. Electrochemical impedance spectroscopy shows that the interfacial impedance of this integrally formed composite film is only 1 / 3 of that of a conventional mechanically bonded bilayer film of the same size, and the total ionic conductivity is 8.0 × 10⁻⁶. -4 The density is S / cm, with an initial density of 80%, which increases to 88% after compaction at 500 MPa.

[0091] Example 7: Preparation of oxide / halide bilayer heterogeneous composite electrolyte film

[0092] First layer printing: Following the formulation and process of Example 3, a first oxide preform film was printed and dried on the PI film without high-temperature heat treatment. Second layer printing: The substrate with the oxide preform film was immersed in the halide Li3YCl6 slurry described in Example 2, and the entire surface was irradiated with ultraviolet light to cure and form a second halide preform film on the oxide layer, followed by drying. Integrated heat treatment: The above-mentioned bilayer composite preform film was subjected to integrated heat treatment at 180°C for 2 hours under argon protection. A dense bilayer oxide / halide composite film was obtained. Cross-sectional SEM showed that the interface between the two layers was blurred and there were no nanoscale cracks. Electrochemical impedance spectroscopy showed that the interfacial impedance of this integrally formed composite film was only 1 / 3 of that of a conventional mechanically bonded bilayer film of the same size, and the total ionic conductivity was 0.6 × 10⁻⁶. -3 The density is S / cm, with an initial density of 79%, which increases to 87% after compaction at 500 MPa.

[0093] Example 8: Preparation of a sulfide / halide / oxide three-layer heterogeneous composite electrolyte film

[0094] First layer printing: Following the formulation and process of Example 3, an oxide preform film is first printed and dried on the PI film without high-temperature heat treatment. Second layer printing: Following the formulation and process of Example 1, a sulfide Li layer is printed and dried on the first preform film. 5.5 PS 4.5 Cl 1.0 Br 0.5 The initial preform film is not subjected to high-temperature heat treatment. Third layer printing: The substrate of the initial preform film is immersed in the halide Li3YCl6 slurry described in Example 2, and irradiated with ultraviolet light to solidify it on the sulfide layer, forming a second halide initial preform film, which is then dried. Integrated heat treatment: The above-mentioned bilayer composite preform film is subjected to integrated heat treatment at 180°C for 2 hours under argon protection. A three-layer heterogeneous composite electrolyte film of sulfide / halide / oxide is obtained. Cross-sectional SEM shows that the interfaces between the three layers are blurred, and there are no nanoscale cracks. Electrochemical impedance spectroscopy shows that the interfacial impedance of this integrally formed composite film is only 1 / 3 of that of a conventional mechanically bonded bilayer film of the same size, and the total ionic conductivity is 1.0 × 10⁻⁶. -3 The density is S / cm, with an initial density of 80%, which increases to 92% after compaction at 500 MPa.

[0095] Comparative Example 1: Wet Coating of Sulfide Solid Electrolyte Membrane

[0096] Under an inert atmosphere, the sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.0 Br 0.5The powder was dispersed in p-xylene solvent, and 2.0 wt% PIB binder was added, wherein the PIB has a fully saturated segmental structure, contains no unsaturated bonds, and has a molecular weight of 8.7 × 10⁻⁶. 5 Mechanically stirred and homogenized the sulfide slurry. After coating using a 150 μm slit, it was heat-treated at 90℃ for 0.5 hours to obtain a dense sulfide solid electrolyte membrane with an average thickness of 45 μm. The thickness deviation at multiple points was ±10 μm. Scanning electron microscopy revealed multiple pores on the membrane surface, and a small amount of foil leakage at the center and edges. The ionic conductivity was 4.0 × 10⁻⁶. -4 S / cm. The initial density was 60%, which increased to 82% after compaction at 500 MPa.

[0097] Comparative Example 2: Preparation of mechanically bonded sulfide / halide bilayer electrolyte films

[0098] The sulfide solid electrolyte membrane and halide electrolyte membrane obtained in Examples 1 and 2 were bonded together and pressurized using a hydraulic press with vertical force applied at a pressure of 300 MPa for 5 minutes to obtain a mechanically bonded double-layer electrolyte film. Cross-sectional SEM showed a significant micron-sized gap between the two layers, and the gap size was uneven. The total ionic conductivity was 1.0 × 10⁻⁶. -3 S / cm, after compaction at 500 MPa, the density increases to 89%.

[0099] As can be seen from the above description, Examples 1 to 3 respectively demonstrate the application of different solid electrolytes in 3D printing electrolyte films, illustrating the universality of the slurry design and special photocuring-heat treatment process route proposed by the present invention for different solid electrolyte characteristics to solid electrolytes.

[0100] Comparing the results of Examples 1-3 with Comparative Example 1, it can be seen that traditional wet coating methods result in poor film thickness accuracy, the appearance of voids, and low density. The thickness deviations in Examples 1-3 were all controlled within ±1 μm. Figure 1 The thickness of the film obtained in Comparative Example 1 was ±10 μm, while that of the other example was ±10 μm. Furthermore, the film thickness obtained in Comparative Example 1 using a 150 μm slit was 45 μm, much smaller than the slit width. The actual film thickness was difficult to control precisely because Comparative Example 1 relied on the doctor blade gap and slurry rheology for thickness control, and the uncontrollable shrinkage of the solvent during drying further amplified the error. Examples 1-5, on the other hand, used ultraviolet light to induce instantaneous cross-linking and curing of an adhesive containing unsaturated double bonds. The curing depth was determined by the light penetration distance in the slurry, obeying the Beer-Lambert law. The thickness could be precisely set by wavelength and light intensity, transforming it into a controllable optical parameter, thus achieving ±1 μm accuracy at the tens of micrometer scale. Simultaneously, immersion printing allowed the edge slurry to be polymerized and "frozen" before surface tension caused shrinkage, fundamentally eliminating the short-circuit risk caused by exposed foil at the center / edge in Comparative Example 1. Figure 2 (No leaking foil).

[0101] The difference between density and ionic conductivity also stems from the curing mechanism. Comparative Example 1 forms a film through solvent evaporation, but solvent migration leaves behind numerous capillary pores. Even after compaction at 500 MPa, the density is only 82%, and the ionic conductivity is only 4.0 × 10⁻⁶. -4 S / cm. In Examples 1-3, the instantaneous photocuring polymer network uniformly anchored the electrolyte particles, with initial densities of 85%, 85%, and 91%, respectively, significantly higher than the 60% of the comparative example. During subsequent heat treatment, the binder further cured, and the particles fused together, forming continuous and dense ion conduction channels. The sulfide film in Example 1 achieved a density of 97% after compaction, with an ionic conductivity of 6.8 × 10⁻⁶. -3 The S / cm ratio was increased by 17 times compared to the control group, proving that the photocuring-thermal treatment route significantly reduced grain boundary impedance.

[0102] Example 4 further utilizes DLP digital photopolymerization to construct a micropillar array on the surface of LATP film in one step, completing the surface morphology customization and film forming simultaneously, effectively increasing the interfacial contact area and providing physical anchoring points, which is difficult to achieve with traditional coating.

[0103] Example 5 combines layer-by-layer photocuring with integrated co-heat treatment, where the first sulfide preform film and the second halide slurry form a network interlock at the interface. Figure 3 A mid-interface fusion layer ensures seamless interlayer bonding. The interfacial impedance of this composite film is only 1 / 3 that of traditional mechanically bonded components, and its total ionic conductivity remains at 1.8 × 10⁻⁶. -3 S / cm breaks through the limitations of traditional thermodynamics and successfully integrates the advantages of different electrolytes.

[0104] Furthermore, this invention tested the assembled batteries using the solid electrolytes obtained in the embodiments and comparative examples. Specifically, the cycle test and rate test were conducted using a mold battery form, employing a Li-In||electrolyte membrane|| composite cathode configuration, with NCM811 as the active material. The test pressure was 2 MPa, the test temperature was 25°C, and the voltage range was 2.8~4.2 V. The initial impedance of the full cell was obtained by fitting after EIS testing, with a test pressure of 2 MPa, a test temperature of 25°C, and a test frequency range of 1 Hz~1 MHz.

[0105] The test results are shown in Table 1 below: Table 1

[0106] As shown in Table 1, the initial impedance of the monolayer membranes in Examples 1-4 was significantly lower than that in Comparative Example 1, with the patterned LATP membrane in Example 4 exhibiting the lowest impedance (6.9 Ω·cm). 2This indicates that the surface micropillar array effectively increases the solid-solid contact area; simultaneously, the cycling capacity retention and rate performance of Examples 1-4 are superior to Comparative Example 1, proving that the photocuring-sintering process improves ion conduction and interface stability by increasing density and eliminating edge foil exposure. Comparing Comparative Example 2 with Examples 5-8, the mechanically bonded bilayer film exhibits a capacity retention of only 58% and a 1C retention of only 30% after 500 cycles, with an impedance as high as 15.4 Ω·cm. 2 The impedance of the in-situ co-sintered composite film decreased to 8.1~9.0 Ω·cm. 2 The cycle retention rate reached 89%~92%, and the 1C retention rate reached 75%~78%. This indicates that the seamless interlocking interface built by layer-by-layer photopolymerization printing combined with the integrated co-firing structure significantly reduces the heterogeneous interface impedance and significantly improves the long-cycle stability and rate performance of the composite solid-state battery.

[0107] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a solid electrolyte, characterized in that, Includes the following steps: S1: Prepare a slurry containing solid electrolyte powder, a binder with unsaturated double bonds, and a solvent; S2: Ensure that the substrate and the slurry are in full contact, and that the slurry coats the surface of the substrate; S3: The substrate coated with the slurry is irradiated with ultraviolet light to cause the binder to crosslink and cure in situ, forming a blank containing the solid electrolyte; S4: The blank is heat-treated to densify it, thereby obtaining a solid electrolyte.

2. The preparation method according to claim 1, characterized in that, The solid electrolyte is selected from at least one of sulfide solid electrolyte, halide solid electrolyte or oxide solid electrolyte; The sulfide solid electrolyte includes at least one of Argyrodite-type sulfide solid electrolyte, thio-LISICON-type sulfide solid electrolyte, or LGPS-type sulfide solid electrolyte; the chemical formula of the Argyrodite-type sulfide solid electrolyte is Li. 6-a PS 5-a X 1+a Where 0 ≤ a ≤ 1, and X includes at least one of Cl, Br, or I; the sulfide solid electrolyte is synthesized using a micro-sulfur excess process, with the excess sulfur molar percentage being 0.5% to 5.0%; The oxide solid electrolyte includes at least one of garnet-type oxide solid electrolyte, perovskite-type oxide solid electrolyte, LISICON-type oxide solid electrolyte, NASICON-type oxide solid electrolyte, anti-perovskite-type oxide solid electrolyte, or LiPON-type oxide solid electrolyte. The general formula of the halide solid electrolyte is A a -M m -X b Wherein, A is selected from Li or Na, M is selected from one or more of Sc, Y, La-Lu, Zr, Hf, Nb, Ta, Al, Ga, In, Mg, Mn, Fe, Co, Zn or Cd, and X is selected from at least one of F, Cl, Br or I.

3. The preparation method according to claim 2, characterized in that, When the solid electrolyte is selected from sulfide solid electrolytes, the solvent is selected from at least one of toluene, xylene, cyclohexane, n-heptane, butyl acetate, ethyl propionate, isobutyl isobutyrate, butyl hexanoate, dibutyl ether, anisole, or 3-heptanone, and the slurry does not contain a photoinitiator; the mass ratio of the sulfide solid electrolyte, binder, and solvent is (10~70):(0.5~20):(30~90); When the solid electrolyte is selected from a halide solid electrolyte, the solvent is selected from at least one of toluene, xylene, cyclohexane, n-heptane, butyl acetate, ethyl propionate, isobutyl isobutyrate, butyl hexanoate, dibutyl ether, anisole, or 3-heptanone. The slurry further includes a first photoinitiator; the first photoinitiator is selected from at least one of benzoin dimethyl ether, 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, benzophenone, or isopropylthioxanthone; wherein the mass ratio of the halide solid electrolyte, binder, first photoinitiator, and solvent is (30~60):(0.5~10):(0.01~2):(30~70). When the solid electrolyte is selected from oxide solid electrolytes, the solvent is selected from at least one of acetonitrile, anisole, chloroform, dichloroethane, N,N-dimethylformamide, toluene, xylene, cyclohexane, n-heptane, butyl acetate, ethyl propionate, isobutyl isobutyrate, butyl hexanoate, dibutyl ether, anisole, or 3-heptanone. The slurry also includes a second photoinitiator; the second photoinitiator is selected from at least one of α-hydroxy ketone photoinitiators, benzoyl ketal photoinitiators, acylphosphine oxide photoinitiators, benzophenone photoinitiators, or thioxanthone photoinitiators; wherein, the mass ratio of the oxide solid electrolyte, binder, second photoinitiator, and solvent is (30~60):(0.5~10):(0.01~2):(30~70).

4. The preparation method according to any one of claims 1 to 3, characterized in that, The binder containing unsaturated double bonds is selected from at least one of the following: modified polyisobutylene, modified hydrogenated nitrile butadiene rubber, modified nitrile butadiene rubber, modified polyacrylic acid, modified polymethyl methacrylate, modified styrene-ethylene-butene-styrene block copolymer, modified styrene-butadiene rubber, modified hydrogenated styrene-butadiene rubber, modified styrene-ethylene-ethylene-propylene-styrene block copolymer, modified polyimide, modified polyvinylidene fluoride, modified butyl rubber, modified polytetrafluoroethylene, modified polypropylene, modified polyethylene, modified cis-butadiene rubber, modified vinyl polybutadiene rubber, modified isoprene rubber, modified ethylene propylene diene monomer (EPDM) rubber, or modified ethylene propylene diene monomer (EPDM) rubber. The molecular weight of the binder containing unsaturated double bonds is 1×10⁻⁶. 4 ~1×10 8 ; The unsaturated double bond content in the binder is 0.1-15% by mass; the content of the unsaturated double bond is determined by the iodine value method.

5. The preparation method according to any one of claims 1 to 4, characterized in that, The substrate includes at least one of copper foil, aluminum foil, stainless steel foil, carbon-coated aluminum foil, PET, PI, PP or PE; The thickness of the substrate is 5~30 μm; The substrate being in full contact with the slurry is defined as immersing the substrate in the slurry.

6. The preparation method according to any one of claims 1 to 5, characterized in that, The wavelength of the ultraviolet light irradiation is 200~400 nm; the duration of the ultraviolet light irradiation is 0.1 s~600 s; The heat treatment is carried out under an argon or nitrogen protective atmosphere, the temperature of the heat treatment is 50℃~300℃, and the time of the heat treatment is 0.1~24h. The steps of preparing the slurry, ensuring full contact between the substrate and the slurry, and irradiating with ultraviolet light are carried out in a dry environment with a dew point below -40°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that, Step S4 of the preparation method is as follows: After step S3 is completed and a blank containing the solid electrolyte is obtained, the blank is immersed again in a slurry containing a different type of solid electrolyte powder than that in step S1, so that the slurry is in full contact with the surface of the blank, and ultraviolet light is applied to allow the latter layer of slurry to penetrate into the micropores of the former layer of blank and solidify, forming a multilayer composite blank; then the multilayer composite blank is heat-treated to form an interface transition zone between adjacent electrolyte layers, resulting in a multilayer heterogeneous solid electrolyte containing at least two layers of different solid electrolytes.

8. A solid electrolyte, characterized in that, Prepared according to the preparation method according to any one of claims 1 to 7; The solid electrolyte comprises solid electrolyte particles and a crosslinked binder network, which is formed by crosslinking and curing of a polymer containing unsaturated double bonds under ultraviolet light and heat treatment.

9. The solid electrolyte according to claim 8, characterized in that, The solid electrolyte comprises a multilayer heterostructure of at least two layers of different solid electrolyte materials, with an interface transition region between adjacent electrolyte layers.

10. A solid-state battery, characterized in that, It includes a positive electrode, a negative electrode, and a solid electrolyte disposed between the positive electrode and the negative electrode, wherein the solid electrolyte is a solid electrolyte prepared according to the preparation method of any one of claims 1 to 7 or the solid electrolyte of claim 8 or 9.